2007
DOI: 10.1002/cbic.200600515
|View full text |Cite
|
Sign up to set email alerts
|

Oligoribonucleotide Analogues Containing a Mixed Backbone of Phosphodiester and Formacetal Internucleoside Linkages, Together with Vicinal 2′‐O‐Methyl Groups

Abstract: Oligoribonucleotides containing formacetal internucleoside linkages have been prepared and studied by UV melting experiments. In RNA duplexes, the formacetal substitution is stabilizing (Deltat(m)=0 to +0.9 degrees C per modification) at physiological salt concentrations (0.1 M) but destabilizing (Deltat(m)=-0.4 to -0.8 degrees C per modification) at high salt concentrations (1 M); this suggests that reduction of electrostatic repulsion contributes substantially to the stabilization. The presence of 2'-O-Me su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 47 publications
7
16
1
Order By: Relevance
“…Matteucci found that formacetals in the DNA strand only slightly decreased the stability of DNA-RNA heteroduplexes 9. In contrast, our preliminary studies showed that formacetals were somewhat stabilizing in all RNA duplexes (+0.2 to +0.8 °C per modification) 4. However, each of these studies used different model sequences, which makes it difficult to compare and rationalize the results.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Matteucci found that formacetals in the DNA strand only slightly decreased the stability of DNA-RNA heteroduplexes 9. In contrast, our preliminary studies showed that formacetals were somewhat stabilizing in all RNA duplexes (+0.2 to +0.8 °C per modification) 4. However, each of these studies used different model sequences, which makes it difficult to compare and rationalize the results.…”
mentioning
confidence: 69%
“…Several modifications, developed earlier to improve the properties of antisense oligonucleotides, have also shown promising results in RNAi 1,2. We are interested in developing RNA analogues having non-ionic internucleoside linkages 3,4. Among such, we have found that replacement of selected phosphates with amide linkages (CH 2 -CO-NH-5′) does not change the overall conformation and thermal stability of RNA 3.…”
mentioning
confidence: 99%
“…The formacetal modification on its own has a stabilising effect on RNA duplexes of 0 to +0.9 8C DT m /mod at physiological salt concentrations, but a destabilising effect (DT m /mod À0.4 to À0.8 8C) at high salt concentrations. The presence of the additional 2'-OMe modification combined with the form-A C H T U N G T R E N N U N G acetal modification had a stabilising effect of +0.5 to +1.9 8C DT m /mod compared to native RNA duplexes [5] (Scheme 2). The Sekine group used a 2'!5' squaryldiamide linkage to create the TpT dimer analogue U 2 -sq 5 -T (6), as replacement of the phosphodiester backbone of DNA.…”
Section: Backbone Modificationsmentioning
confidence: 97%
“…Many moieties that are not chemically similar to phosphodiester, such as amide, guanidine and acetal have been used to replace the phosphodiester linkage. [1] More recently Strçmberg et al explored the combination of formacetal linkages and 2'-OMe modifications in oligoribonucleotides (5). The formacetal modification on its own has a stabilising effect on RNA duplexes of 0 to +0.9 8C DT m /mod at physiological salt concentrations, but a destabilising effect (DT m /mod À0.4 to À0.8 8C) at high salt concentrations.…”
Section: Backbone Modificationsmentioning
confidence: 98%
“…Phosphorus (V) esters and acetals are both tetrahedral and approximately isosteric, and it is known that aNAs can base pair with RNAs (Matteucci and Bischofberger 1991). Specifically, point substitutions of this linkage impart a modest destabilization to DNA-DNA and DNA-RNA duplexes and show saltdependent effects on RNA-RNA duplexes (stabilization at low salt, destabilization at high salt) (Jones et al 1993;Rice and Gao 1997;Rozners et al 2007;Kolarovic et al 2009). …”
Section: Primitive Genetic Polymersmentioning
confidence: 99%